Análisis jurídico de las tarifas del impuesto sobre la renta - Cervantes Martínez, Juan (Universidad Michoacana de San Nicolás de Hidalgo, 2011)
Any contribution, to have constitutional validity, must respect the guiding principles established by the Supreme Law Policy -Constitution Federal- in other words the laws that emanate from it should be subject to the provided by the Constitution, especially the provisions of the Article 31, section IV of the Constitution, which establishes ... the obligation of Mexicans to contribute to public expenditure in the manner provided by law, be framed and the principle of legality, which must be respected by the Mexican tax system. The tax system in force in Mexico, while acknowledging the rule of law as the core of the contributions, no doctrinal and jurisprudential content resulting in the violation of fundamental rights of taxpayers and creating tax institutes outside the criteria legality and justice. The lack of knowledge and appreciation of this principle has caused some tributes lack of legality, that is the maximum the principle of legality which the doctrine has developed for study on the principle of law-book notes that only the legislator -through the legislative-process is empowered by the Constitution to establish the contributions, in addition to the obligation to set all the essential elements to determine the tax liability in a sure and certain. Such lack of legality taxes shown in the income tax of individuals, which states that through tariffs individuals determine the tax. Applicable to Title IV of the law in question rates, do not adhere to the principle of legality, since only mention the objective of the -Appearance rates beginning-ignoring describe how individuals should apply those rates -Appearance subjective- fact that, besides being very unfortunate, is of constitutional illegitimacy of these tax figures.

Toda contribución, para que tenga validez constitucional, debe respetar los principios rectores establecidos en la Ley Suprema –Constitución Política Federal– dicho en otras palabras las leyes que emanen de ella deben sujetarse a lo proveído por la Constitución, en especial a lo establecido en el Articulo 31, fracción IV Constitucional, que establece…la obligación de los mexicanos de contribuir para los gastos públicos de la manera que dispongan las leyes, enmarcándose así, el principio de legalidad, que debe ser respetado por el sistema tributario mexicano. El sistema tributario que rige en México, aun cuando reconoce el principio de legalidad como eje de las contribuciones, carece doctrinal y jurisprudencialmente de contenido dando como resultado la vulneración de los derechos fundamentales de los contribuyentes y la creación de institutos tributarios al margen de los criterios de legalidad y justicia. La falta de conocimiento y valoración de este principio ha ocasionado que algunos tributos carezcan de legalidad, es decir la máxima del principio de legalidad –que la doctrina lo ha desarrollado para su estudio, en el principio de reserva de ley– señala que sólo el legislador –a través del proceso legislativo– es el facultado por la Constitución para establecer las contribuciones, además de tener la obligación de configurar todos los elementos esenciales que permitan determinar la obligación tributaria de forma cierta y segura. Este tipo de tributos carentes de legalidad se aprecia en el Impuesto sobre la Renta de las personas físicas, el cual establece que a través de tarifas las personas físicas determinaran dicho Impuesto.
Facultad de Contaduría y Ciencias Administrativas. Maestría en Fiscal
Keywords: info:eu-repo/classification/cti/5; FCCA-M-2011-0176; ISR; Principio de legalidad; Gastos públicos; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/5966